(untitled) (Praxis Educativa, 2018)
Internships play a substantial place in the curriculum of the technical schools as a training strategy for students and as a possibility to approach the world of work. This article addresses the general features of the enactment of the internship in companies for the professional training of students of a technical school in the city of Cordoba (Argentina). From a case study, based on obtaining primary data (interviews to the management team, students, and employers) and the analysis of secondary data (ministerial and institutional documents); it was possible to identify that in the enactment of the internship, the school trajectory and the academic performance of the students act as selection mechanisms for the completion of the internships in certain companies. Consequently, the form of access in the internship system generates differentiated and inequitable practices in the training of students. The company they attend is a factor that influences their training and their expectations regarding the possibility of a quick entry to the world of work.